A universal measure of chaotropicity and kosmotropicity. (12th November 2012) - Cray, Jonathan A.; Russell, John T.; Timson, David J.; Singhal, Rekha S.; Hallsworth, John E.
Summary Diverse parameters, including chaotropicity, can limit the function of cellular systems and thereby determine the extent of Earth's biosphere. Whereas parameters such as temperature, hydrophobicity, pressure, pH, Hofmeister effects, and water activity can be quantified via standard scales of measurement, the chao‐/kosmotropic activities of environmentally ubiquitous substances have no widely accepted, universal scale. We developed an assay to determine and quantify chao‐/kosmotropicity for 97 chemically diverse substances that can be universally applied to all solutes. This scale is numerically continuous for the solutes assayed (from +361 kJ kg−1 mol−1 for chaotropes to −659 kJ kg−1 mol−1 for kosmotropes) but there are key points that delineate (i) chaotropic from kosmotropic substances (i.e. chaotropes ≥ +4; kosmotropes ≤ −4 kJ kg−1 mol−1); and (ii) chaotropic solutes that are readily water‐soluble (log P < 1.9) from hydrophobic substances that exert their chaotropic activity, by proxy, from within the hydrophobic domains of macromolecular systems (log P > 1.9). Examples of chao‐/kosmotropicity values are, for chaotropes: phenol +143, CaCl2 +92.2, MgCl2 +54.0, butanol +37.4, guanidine hydrochloride +31.9, urea +16.6, glycerol [> 6.5 M] +6.34, ethanol +5.93, fructose +4.56; for kosmotropes: proline −5.76, sucrose −6.92, dimethylsulphoxide (DMSO) −9.72, mannitol −6.69, trehalose −10.6, NaCl −11.0, glycine −14.2, ammonium sulfate −66.9, polyethylene glycol‐ (PEG‐)1000 −126; and for relatively neutral solutes: methanol, +3.12, ethylene glycol +1.66, glucose +1.19, glycerol [< 5 M] +1.06, maltose −1.43 (kJ kg−1 mol−1). The data obtained correlate with solute interactions with, and structure–function changes in, enzymes and membranes. We discuss the implications for diverse fields including microbial ecology, biotechnology and astrobiology.